Formal requirements for the recognition and enforcement of judgments in accordance with the convention on judicial assistance in civil and commercial matters signed between Algeria and Spain: notes to the judicial decree of the provicial court of Valen - Merchán Murillo, Antonio (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The present study shows the formal needs for the recognition and execution of a judgement issued by an Algerian court. However, from the perspective of the res judicata, the incidence of the previous divorce decision must be shown in this matter.
Keywords: judicial decree; appeal; exequatur procedure; Provincial Court